Hyperglycemia on hospital admission as a predictor of poor outcome in patients hospitalized for COVID-19: Hiperglicemia al ingreso hospitalario como predictor de mala evolución en pacientes hospitalizados por COVID-19 - Cuba-Ticona , Shellsy L. (2024)
Introduction: SARS-CoV-2 virus causing COVID-19 disease, was first discovered in Wuhan, China in December 2019. Peru was one of the countries with the most alarming figures. The mortality rate as of April 13, 2023 was 674.3.Regionally,the city of Moquegua ranked fourth with a figure of 891. 9 preceded by Callao, Ica and Metropolitan Lima and was associated with various risk factors, such as hyperglycemia Objective: To determine whether hyperglycemia on admission is a prognostic factor for unfavorable outcome in patients hospitalized with COVID-19 at the Regional Hospital of Moquegua during the first and second epidemiological wave of SARS-CoV-2.Materials and methods: An observational, analytical, cohort, retrospective study was carried out with the application of a data collection form. A sample of 640 medical records was obtained by simple random probability sampling. Data processing was carried out using Microsoft Excel and the SPSS statistical program to obtain frequencies, crude RR, adjusted RR and significance. Results: The higher the glycemia at admission, the higher the risk of unfavorable outcome (RRa: 5.649, 95%CI: 3.717 - 8.620, p: <0.001) and respiratory sequelae (RRa=1. 958; 95%CI:1.736-2.208 p 0.000), admission to ICU (RRa=3.683; 95%CI :2.027-6.691 p 0.000), and death (RRa=1.568; 95%CI :1.216-2.023 p 0.001). Conclusions: Hyperglycemia is a risk factor for poor prognosis (respiratory sequelae, ICU admission and death).